HIV/AIDS Prevention through Pocketbook to Increase Knowledge and Attitudes Among Adolescents - Rafika Fajrin; Yustina Tyas Kurniawati; May Lorenna; Agustin Setianingsih (GLOBAL HEALTH SCIENCE GROUP, 2024)
Adolescent reproductive health is a health condition that concerns to reproductive system, functions, and processes owned by adolescents. HIV attacks the immune system then AIDS is a symptom of reduced self-defense caused by the entry of HIV. Objective: to determine the effect of communication, information, and education methods using pocketbooks to increase adolescents' knowledge and attitudes about health as a preventive effort for HIV/AIDS at SMA Negeri 4 Semarang. Method: This quantitative research used the quasi-experimental method with one group pre-post test design. The sampling technique was a total sampling of 52 students. The instrument used was a questionnaire measuring the knowledge and attitude of adolescents. Results: statistical tests using the Wilcoxon Test with a Paired T-test. The majority of those aged 15-18 years (69%) and dominated by women (52%) showed that before the intervention with education using pocketbook, the level of knowledge was good and sufficient at 50% each. After the intervention, there was an increase in good knowledge to 73.1%. Before the intervention, the majority of respondents had a good attitude of 65.4% but after the intervention, there was an increase to 73%. Bivariate analysis showed the effect of pocketbook media on increasing knowledge and attitudes of adolescents about HIV/AIDS with a p-value of 0.116 and 0.023, respectively. Conclusions: Using pocketbooks significantly improves adolescents' knowledge and attitudes regarding HIV/AIDS, highlighting their effectiveness in conveying health information.